2020
DOI: 10.1161/hypertensionaha.120.14957
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Value of Angiogenic Markers in Twin Pregnancies to Predict Delivery Due to Maternal Complications of Preeclampsia

Abstract: The sFlt-1 (soluble fms-like tyrosine kinase-1), PlGF (placental growth factor), and their ratio are useful for predicting delivery because of preeclampsia in singleton pregnancies. Evidence on the utility of sFlt-1/PlGF ratio in twin pregnancies is lacking. We aimed to evaluate the predictive value of sFlt-1/PlGF ratio for delivery because of preeclampsia in twins. A retrospective data analysis of 164 twin pregnancies with suspected preeclampsia was performed. The sFlt-1/PlGF ratio, which was known to clinici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 23 publications
4
30
1
2
Order By: Relevance
“…Our exploratory prediction performance analysis indicates that using a cutoff of 38 for the sFlt-1/PlGF ratio has an NPV of 91.9 and 83.8% to rule out PE within 1 and 4 weeks, respectively, in women with twin pregnancies and suspected PE. This is in agreement with the study by Binder et al [31] which determined that using a cutoff of 38 for the sFlt-1/PlGF ratio has an NPV of 98.8 and 96.4% to rule out PE within 1 and 2 weeks, respectively. As failure to detect PE can have serious clinical implications, a very high NPV is crucial when assessing patients with suspected PE.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our exploratory prediction performance analysis indicates that using a cutoff of 38 for the sFlt-1/PlGF ratio has an NPV of 91.9 and 83.8% to rule out PE within 1 and 4 weeks, respectively, in women with twin pregnancies and suspected PE. This is in agreement with the study by Binder et al [31] which determined that using a cutoff of 38 for the sFlt-1/PlGF ratio has an NPV of 98.8 and 96.4% to rule out PE within 1 and 2 weeks, respectively. As failure to detect PE can have serious clinical implications, a very high NPV is crucial when assessing patients with suspected PE.…”
Section: Discussionsupporting
confidence: 93%
“…While we found no statistically significant differences in the sFlt-1/PlGF ratios between monochorionic and dichorionic twin pregnancies, in agreement with Binder et al [31], Faupel-Badger et al [9] suggest that monochorionic twin pregnancies have higher values of sFlt-1 and sFlt-1/PlGF ratios. This discrepancy may be due to the low number of cases in the study by Faupel-Badger et al [9] ( n = 5 monochorionic pregnancies; n = 36 dichorionic pregnancies).…”
Section: Discussionsupporting
confidence: 92%
“…33 Recently, Binder et al 33 showed the applicability of the cutoff of 38 to rule out a delivery because of PE in twin pregnancies for 1 and 2 weeks at an NPV of 98.8% and 96.4%, respectively. 34 Following single measurements, repeated measurements are important: patients with a delta between 2 measurements 2 and 3 weeks apart have a higher risk of PE. In the group of women that eventually developed PE, the mean delta of the sFlt-1etoePlGF ratio within 2 weeks was 31.2 (interquartile range [IQR], 6.48e62.36), whereas in the group of patients that did not develop PE in the end, it was 1.45 (IQR e0.12 to 9.41).…”
Section: Predictive Cutoffs For Preeclampsiamentioning
confidence: 99%
“…The main biological function of PlGF is to promote the formation of placental blood vessels [ 10 , 11 ]. PlGF is a kind of biomarker.…”
Section: Methodsmentioning
confidence: 99%
“…Bian et al used sFlt-1/PlGF ratio to predict the risk of preeclampsia in Asian women [ 10 ]. PlGF combined with other angiogenesis markers, such as sFlt-1, also had a certain prognostic value for preeclampsia [ 11 , 12 ]. There are also some controversies in related prediction research.…”
Section: Introductionmentioning
confidence: 99%